FORMATION OF POLY-ART SKILLS OF THE FUTURE LEADER OF CHILDREN'S CHOREOGRAPHIC COLLECTION (Pedagogy of Higher and Secondary Education, 2022)
In this article the necessity of formation of highly artistic skills of the future instructor of children's choreographic group in the process of choreographic activities is examined.
Keywords: highly artistic skills; instructor of children's choreographic group; polyfunctional culture; synthetic art; integration of various